An analytical study of Arabic grammar book questions for the second intermediate grade in the light of objectives and content (Journal of the College of Basic Education, 2022)
The current research aims to analyze the Arabic grammar book questions for the second intermediate grade in the light of objectives and content, and the researcher followed the descriptive analytical approach, as the number of the book’s pages reached (139) pages, (55) questions distributed in six chapters, and (16) topics, and after Using the percentage and Scott equation, as it showed that the book's questions focus on the lower cognitive levels of Bloom's classification, especially on the level of knowledge (remembering) than other higher cognitive levels. It is also entitled to sound language in some form, and that the questions do not cover the subject matter